Estudio comparativo de alternativas de fertilizantes para los cultivos de Colombia a partir de la aplicación de la biotecnología. (2022)
The use of chemical fertilizers is of great importance to meet the nutritional needs such as nitrogen, phosphorus and potassium for crops; however, the excessive use of these products causes different environmental problems such as eutrophication; groundwater contamination; air pollution and land degradation. Likewise, health problems arise in people who make use of these agricultural inputs and in those who consume products that were developed with high levels of chemical fertilization, among these are methemoglobinemia and nitrosamines.